Assibi A. Amidu. 2007. Semantic Assignment Rules in Bantu Classes. Review - Dingemanse, Mark (Afrikanistik online, 2008)
It seems not too far off the mark to suggest, as Assibi Amidu does, that descriptions of the semantics of Bantu noun class systems have in the past often been crude oversimplifications of the linguistic facts. In this study, which continues a line of investigation initiated in Amidu (1997), Amidu sets himself the laudable goal of accounting for Swahili noun classification and concord on the basis of real usage.
Keywords: Swahili